Prevalence of gingival diseases, malocclusion and fluorosis in school-going children of rural areas in Udaipur district - Dhar V; Jain A; Van Dyke T; Kohli A (Wolters Kluwer Medknow Publications, 2007)
High prevalence of dental diseases has been recorded in Rajasthan, however, not much work has been done to ascertain the prevalence of dental diseases in Udaipur district. This study was conducted among 1,587 government school children of Udaipur district in the age group of 5-14 years for recording the prevalence of gingival diseases, fluorosis and malocclusion. Gingivitis was found in 84.37% of children, malocclusion in 36.42% and fluorosis in 36.36%.